The Impact Of Knowledge Sharing On Employee Performance Mediated By Individual Innovation Capability - Armansyah, Armasyah; Saputra, Eka Kurnia; Abriyoso, Octojaya; Faris, Salman (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study seeks to explore the influence of knowledge sharing on employee performance, with a focus on how individual innovation capability plays a mediating role. A sample of 88 employees was analyzed using a quantitative research method. Data was collected through both library and field research, utilizing a 36-item questionnaire. Structural Equation Modeling (SEM) was applied to analyze the data, with SmartPLS software assisting in the process. The findings reveal that knowledge sharing positively affects individual innovation capability, which, in turn, enhances individual performance. However, knowledge sharing does not directly impact individual performance, with its influence being partially mediated by individual innovation capability